The Effect of Aerobic Dance Exercise towards the Decreasing of Total Cholesterol Level on Kiyomi Dance Studio’s (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
The purposes of this study are to know the total level cholesterol of the samples before and after doing aerobic dance exercise besides to know the influence of aerobic dance exercise toward reduction of total blood choleterol levels. This is a Pre-Experimental Design study and used One Group Pretest Posttest Design. The population in this study was participants of Kiyomi gymnasium group and 16 participants. The collected data was gathered by measuring blood total cholesterol levels when conducting pre-test and post-test by using East Touch GCU. For analysing the data used Paired T-test. The result of the study shows the average of the samples after doing aerobic dance exercise are able to lower the blood total cholesterol levels from 221,68 to 173,12. And gained tarithmetic as many as 6,197 with the value of signification 0,000 < 0,05. It means that there is a significant influence between aerobic dance exercise and reduction of total cholesterol. The conclusion of this study is there is reduction of the average of the total cholesterol levels before (pre-test) and after getting treatment (post-test) so it can be concluded that there is an effect of aerobic dance exercise toward the decreasing of total cholesterol level on Kiyomi dance studio’s members in Gabus Sub-District Pati Regency.